Assessment of Work Posture During Fresh Fruit Bunch Loading Using REBA and ART to Reduce MSDs Risk - Indah Agustina Sari; Cut Ita Erliana; A. Amri (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The loading activity of Fresh Fruit Bunches (FFB) at the plantation of PT. ALM is still performed manually by lifting, carrying, and throwing the FFB into truck beds. These repetitive activities, combined with non-ergonomic working postures, have the potential to cause Musculoskeletal Disorders (MSDs) among workers. This study aims to determine the level of ergonomic risk in FFB loading activities using the Rapid Entire Body Assessment (REBA) and Assessment of Repetitive Tasks (ART Tool) methods, as well as to propose an ergonomic improvement to reduce the risk of MSDs. Data were collected through observation, documentation, interviews, the Nordic Body Map (NBM) questionnaire, and anthropometric measurements. The results of the NBM questionnaire indicated that workers experienced discomfort in the back, lower back, shoulders, upper arms, and wrists. The REBA analysis showed that the FFB loading activity falls into a high-risk category, requiring immediate corrective action. Similarly, the ART Tool assessment indicated a high level of risk due to repetitive movements, excessive force exertion, and prolonged working duration. Based on the analysis, an ergonomic improvement in the form of a hydraulic FFB transport and dumping trolley was proposed, designed according to the workers' anthropometric data. The proposed trolley has dimensions of 180 cm in length, 100 cm in width, and 140 cm in height, with a carrying capacity of 200–250 kg, equivalent to 8–10 fresh fruit bunches.